SEX RATIO AND SEASONAL ABUNDANCE OF SEABOB SHRIMP Xiphopenaeus kroyeri lato sensu (DECAPODA: PENAEIDAE) IN THE NORTHEASTERN BRAZILIAN COASTAL ECOREGION: Razão sexual e abundância sazonal do camarão sete-barbas Xiphopenaeus kroyeri lato sensu (Decapoda: Penaeidae) na ecorregião costeira do nordeste brasileiro - Melo-Lima, Valeria Maria; Da Mata-Oliveira, Igor; Lucena Frédou, Flavia; Coelho Filho, Petrônio Alves (Arquivos de Ciências do Mar, 2024)
This study evaluated the sex ratio and seasonal abundance of the seabob shrimp Xiphopenaeus kroyeri at the mouth of the São Francisco River, Northeastern Brazil, from 2008 to 2009. A total of 3,072 individuals were collected, measured for carapace length (in mm), and classified by sex and developmental stage. Shrimps were categorized according to the capture period (dry or rainy season). Size distribution ranged from 8-34 mm, with the highest concentration in the 18-20 mm class. Females were significantly more abundant and larger, predominating in most size classes. Juveniles represented 3.5% of the specimens, being more frequent in the dry season. There was no difference in adult participation between the analyzed periods. The dominance of females may be influenced by fishing selectivity, which tends to capture larger individuals. This study provides insights for the sustainable management of X. kroyeri stocks, highlighting the importance of management measures to maintain population viability, especially in the face of overfishing of reproductive stocks. Keywords: Penaeid, sexual dimorphism, length classes, seasonality, Population dynamics.